Impact of Integrated Urban Housing Development Program on Household Poverty Alleviation: Adama City, Oromia Regional National State, Ethiopia - Haji, Jema; Aman, Mohammed; Gebo, Abdela (Asian Journal of Empirical Research, 2013)
In this paper, we investigate the impact of the integrated urban housing development program on poverty alleviation using household’s consumption expenditure as a proxy. For this, primary household level data were collected from 240 randomly selected households, 120 from participants while 120 from non-participants, during the 2011 fiscal year, in Adama city of the Oromia National Regional State, Ethiopia. Using a propensity score matching model, the difference in total consumption expenditure between households who participate and those who do not were evaluated. Besides, the poverty incidence curve and rank in distribution differences was also tested using poverty incidence curve by stochastic dominance. Accordingly, the poverty incidence curve of participant households, at every point, lie below the curve of the non-participants indicating participants were less poor than non-participants. The empirical result of the matching showed that participant households in the integrated urban housing development program have significantly higher consumption expenditure per adult equivalent than the non-participant households. Among the factors assumed to affect the participation of the households in the program, formal years of schooling, work status, birth place and asset ownership have a positive and significant effect. While, sex of the household and prior job, being student and self-employed, have a negative and significant effect. This implies that, empowering women and giving more technical training will induce their participation in the housing development program and hence on household poverty alleviation.